Ethnobotanical Study in the Sianok Canyon Community Agam Regency West Sumatra - Nazhifah, Naura; Kardiman, Reki; Chatri, Moralita; Vauzia, Vauzia; Roza, Sri Yenica (Jurnal Biologi Tropis, 2025)
Ethnobotany describes the direct relationship between humans and plants in traditional use. Ethnobotany has various uses for people with plants, including food, medicine, tools, infrastructure, culture, and small and medium industries in everyday life. This study aims to examine the use of plants in the daily lives of the people of Nagari Sianok, Agam Regency, West Sumatra, through an ethnobotanical approach. The research method used is descriptive qualitative, with data collection techniques through interviews, field observations, and documentation. The results of the study showed that the people of Nagari Sianok utilize 55 plant species from 33 families for various needs, including as cooking spices, traditional medicines, building materials, tools, and customary needs and small household industries. The Zingiberaceae family is the most widely used, followed by Solanaceae, Euphorbiaceae, and Amaryllidaceae. The parts of the plant used include leaves (34.3%), tubers (29.6%), stems (19.1%), fruits (13.3%), flowers (2.2%), and seeds (1.4%). The main sources of raw materials come from markets (68.2%), home gardens (22.9%), and gardens (8.3%). The most widely used species are Curcuma longa (Linn.), Zingiber officinale Roscoe, and Alpinia galanga, which are used as spices and traditional medicines. These results indicate that the people of Nagari Sianok have rich ethnobotanical knowledge and still maintain local wisdom in utilizing plants.